Drogi hańby : piśmiennictwo polskie przełomu XIX i XX wieku o handlu "żywym towarem" - Antonów, Radosław (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2013)
The white slave trade in the 19th and at the beginning of the 20th centuries was called at first the white slave trade, the "living goods" and then the women and children trade. The crime, prosecuted by the state and the international law, hurt severely not only the Polish annexed territories but it also was an essential safety problem of Poland after 1918. The white slave traders used deceit to persuade their victims to go abroad. Well-paid work or marriage were to be the motivation. Both proposals were very tempting, especially as the Polish people on annexed territories were painfully aware of the repressive politics of the partitioners leading to the citizen poverty. It was also the presence of the economic problem after regaining the independence in Poland. It should be emphasized that the "white slave trade" was put in anti-Polish politics of the partitioners. The partitioners stimulated the prostitution development and used secret police surveillance of citizen. Writing about the problem of the white slave trade during the period of the Partitions of Poland as well as all Polish initiatives eradicating the crime before 1918 were prohibited. The authorities of the partitioners considered the problem the political issue and it was the partitioners service who makes the final decision. Such approach of the partitioners enabled the uncontrolled development of the white slave trade from the Polish territories so the "polacca" name was in Argentina the synonym of a prostitute. Despite the prohibition quite a lot of valuable publication on the subject appeared, which are contained in the book. They served as information and revealing material about the white slave trade practice. Combating the trade and political, legal social and medical research of the white slave trade problem developed in Poland only after regaining the independence. The book also contained some publication of that period.
Keywords: handel ludźmi; przemyt ludzi; praca przymusowa